Effect of Dolomite and NPK on The Growth and Yield of off-Season Shallots - Iswahyudi, Iswahyudi; Haryanto, Eddy Tri; Supriyono, Supriyono; Al-batul, Fitrotunnisa; Samanhudi, Samanhudi; Irawati, Erni; Rahayu, Muji; Purwanto, Edi (Akademi Komunitas Perkebunan Yogyakarta, 2026)
Shallot is a high-value horticultural commodity. Its productivity often declines due to suboptimal soil conditions, such as low pH and imbalanced nutrient availability, especially when cultivated off-season. This study aimed to determine the optimal combination of dolomite and NPK (Nitrogen, Phosphorus, Potassium) fertilizer for the growth and yield of shallot cultivated in the off-season. The research was conducted in Ngringo Village, Jaten District, Karanganyar Regency from February-April 2025. The method used was a factorial Completely Randomized Design (CRD) with two factors and three replications. The first factor was dolomite doses (0; 2000; and 4000 kg.ha-1) and NPK fertilizer doses (250; 375; and 500 kg.ha-1). Observed parameters were plant height, number of leaves, fresh and dry biomass weight, fresh and dry bulb weight, number of bulbs per plant, and bulb diameter. Data were analyzed by analysis of variance (ANOVA) at a 95% significance level and continued with Duncan’s Multiple Range Test (DMRT) with 95% significance level when significant differences were found. The results showed no significant interaction between dolomite and NPK fertilizer on shallot growth and yield. Dolomite at 2000 kg.ha-1 significantly increased the number of leaves, while NPK fertilizer had no significant effect. However, 250 kg.ha-1 of NPK fertilizer produced similar results to higher doses, indicating potential fertilizer efficiency. Environmental conditions such as high humidity and low light intensity likely influenced treatment effectiveness.